Apresiasi Perempuan Muslim Pasirjati Terhadap Persoalan Kesehatan Bayi dan Balita: The Appreciation of Muslim Women in Pasirjati Toward Infant and Toddler Health Issues - M. Khusna Amal (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2002)
Despite adequate health facilities in urban Pasirjati, Muslim mothers showed low appreciation for infant and child health, highlighting a critical socio-medical paradox. Grounded in Dahrendorf's Conflict Theory, the study examined gender-based social structures to identify the sociocultural determinants of this low appreciation. Using qualitative methods—including observation, in-depth interviews, and documentation—with informants such as mothers, village officials, and religious leaders, the research explored how power imbalances shape health practices. Findings revealed that mothers were assigned exclusive, uncritical responsibility for child health due to patriarchal social construction. Key contributing factors included low economic status and limited education, which restricted access to information and self-empowerment. Consequently, appreciation for essential nutrition, intensive care, and preventive health behaviours remained minimal. The study concludes that gender-biased social structures, rather than biological determinism, perpetuate health disparities. Recommendations include empowering Muslim women through education and involving men in child health responsibilities to foster more equitable and constructive social relations. Meskipun fasilitas kesehatan di daerah perkotaan Pasirjati memadai, apresiasi ibu Muslim terhadap kesehatan bayi dan balita tergolong rendah, sehingga menjadi paradoks sosial-medis yang krusial. Berlandaskan Teori Konflik Dahrendorf untuk mengkaji struktur sosial berbasis gender, penelitian ini bertujuan mengidentifikasi determinan sosiokultural dari rendahnya apresiasi tersebut. Dengan metode kualitatif—meliputi observasi, wawancara mendalam, dan dokumentasi—kepada informan seperti ibu, aparat kelurahan, dan tokoh agama, penelitian mengeksplorasi bagaimana ketimpangan kuasa membentuk praktik kesehatan. Temuan menunjukkan bahwa ibu memegang tanggung jawab penuh dan tidak kritis terhadap kesehatan anak akibat konstruksi sosial patriarkis. Faktor utama penyebabnya adalah status ekonomi rendah dan tingkat pendidikan yang minim, yang membatasi akses terhadap informasi dan pemberdayaan diri. Akibatnya, apresiasi terhadap gizi esensial, perawatan intensif, dan perilaku kesehatan preventif sangat rendah. Kesimpulannya, struktur sosial bias gender, bukan faktor biologis, yang melanggengkan kesenjangan kesehatan. Rekomendasi mencakup pemberdayaan perempuan Muslim melalui pendidikan dan pelibatan laki-laki dalam tanggung jawab kesehatan anak demi terciptanya relasi sosial yang lebih konstruktif dan adil.